Development and characterization of an intraocular biodegradable polymer system containing cyclosporine-A for the treatment of posterior uveitis - Juliana Barbosa Saliba; André Augusto Gomes Faraco; Maria Irene Yoshida; Wander Luiz de Vasconcelos; Armando da Silva-Cunha; Herman Sander Mansur (Materials Research, 2008)
The aim of this study was to synthesize and characterize the biodegradable intraocular implants based on poly (D,L-lactide-co-glycolide) (PLGA 75:25) with Cyclosporine-A (CyA) and to evaluate their in vitro drug delivery profile. Thermal analysis was conducted by using Thermogravimetry (TG) and Differential Scanning Calorimetry (DSC). Phase analysis and crystallinity of the polymer-CyA samples were assessed through X ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Finally, microstructure and morphology of the systems were investigated by Scanning Electron Microscopy (SEM). The results showed that CyA was successfully incorporated into PLGA network with drug loading of approximately 31.6%. Also, based on FTIR and thermal analyses (TGA/DSC) no significant physical-chemical interaction was detected at the micro-nanoscale level between polymer/drug. SEM micrographs have indicated a uniform drug distribution in PLGA matrix. XRD patterns have showed that the incorporated semi-crystalline structure of CyA has not significantly altered the polymeric mainly amorphous network. In addition, the results have confirmed the chemical and biological drug stability, the drug distribution into the polymeric matrix and the possibility of cyclosporine prolonged delivery system profile.